PERANCANGAN TATA LETAK FASILITAS KANTOR PPIC MENGGUNAKAN METODE ARC, ARD, DAN SRD PADA PERUSAHAAN MANUFAKTUR KERAMIK DI JAWA TIMUR - Aan Hadinata; Ramadhani Erik; Nur Qidam Aliyanto; Ida Kusnawati Thjahjani (Program Studi Teknik Industri Universitas Teknologi Sumbawa, 2026)
One of the ceramic manufacturing companies in East Java has not yet optimized the layout of its Production Planning and Inventory Control (PPIC) office facility, resulting in inefficient coordination, document flow, and supervision among personnel. This study aims to develop a proposed facility layout for the PPIC office by integrating the Activity Relationship Chart (ARC), Activity Relationship Diagram (ARD), and Space Relationship Diagram (SRD) methods. A descriptive qualitative approach was used, with data collected through direct observation and interviews. Eight work areas were identified: the Manager’s Desk, Head of Department’s Desk, Assistant Manager’s Desk, Staff Work Area, Raw Material Document Warehouse, Finished Goods Document Warehouse, Staff Document Cabinet, and Meeting Table. Space requirements were calculated by adding a 10% allowance and multiplying by an ASLE factor of 2.1, yielding a total actual space requirement of 554,862 cm² (55.49 m²). The ARC analysis identified the Staff Work Area as the node with the highest connectivity. The proposed layout resulting from the ARD and SRD integration is expected to improve coordination, supervision, communication, and document flow within the PPIC office. It is concluded that the integration of ARC, ARD, and SRD is effective as a basis for designing a more efficient PPIC office facility layout.